Gross and microscopic changes of liver neoplasms and background hepatic structures following neoadjuvant therapy. Issue 2 (22nd January 2019) - Hodgson, Anjelica; Almansouri, Zuhoor; Adeyi, Oyedele; Fischer, Sandra E
Abstract : Liver transplantation is a surgical option with curative intent used in the management of some cases of hepatocellular carcinoma and cholangiocarcinoma (hilar, rarely intrahepatic). A number of different therapeutic modalities including ablative techniques, arterially directed therapies, radiation and chemotherapy are used in the neoadjuvant setting prior to liver transplantation with the goals of preventing tumour progression, decreasing post-transplant recurrence and possibly downstaging patients with tumour burden beyond what is acceptable by current transplant criteria. Pathologists evaluating hepatic explants must be aware of these neoadjuvant therapies and the alterations induced by them in both tumourous and non-tumourous tissue. In this review, we discuss common neoadjuvant therapies used in in this setting, as well as the gross and microscopic changes induced by these presurgical treatments within hepatic neoplasms as well as the background hepatic parenchyma and nearby structures. Select secondary tumours involving the liver which are pretreated will also be discussed. Finally, proper reporting of these changes will be mentioned.